Efficacy and Safety Aspects of Remifentanil Sedation for Intubation in Neonates: A Retrospective Study - Chollat, Clément; Maroni, Arielle; Aubelle, Marie-Stéphanie; Guillier, Cyril; Patkai, Juliana; Zana-Taïeb, Elodie; Keslick, Aurélie; Torchin, Héloïse; Jarreau, Pierre-Henri (Frontiers in Pediatrics, 2019)
Objective: To evaluate the efficacy and safety of remifentanil as a premedication in neonates undergoing elective intubation. Study Design: This retrospective study focused on neonates admitted to the Neonatal Intensive Care Unit of Port-Royal, Paris Centre University Hospitals, France, between June 2016 and November 2017, who received remifentanil before an elective intubation. First, atropine (10 µg/kg) was administered intravenously as a bolus, followed by remifentanil, which was administrated continuously. The dose of remifentanil was reduced twice during the study period in order to administer the minimum effective dose and thus reduce possible adverse events. Results: Fifty-four neonates were exposed to remifentanil and atropine. The intubating conditions were excellent or good for 46 procedures (85%) and the median Acute Pain in Newborn Infants score was 2 (IQ 25-75: 0-5) before the sedation, 1 (0-2) during the laryngoscopy, and 0 (0-0) after the intubation. The intubation was successful at the first attempt for 18 patients (33%). Chest wall rigidity occurred in 6 procedures (11%), other respiratory problems in 5 (9%), and laryngospasm in 1 (2%). Some of the procedures were complicated by bradycardia (23%) or desaturation (37%). Conclusions: Remifentanil and atropine prior to intubation provided satisfactory intubating conditions in neonates. Nevertheless, severe adverse effects (such as chest wall rigidity) are a potential risk, possibly related to the total dose received. These data do not support the safety of using remifentanil alone prior to intubation in neonates.